Working the Phones Control and Resistance in Call Centres - Woodcock, Jamie (Pluto Press, 2016)
*Shortlisted for the BBC Radio 4 Thinking Allowed Award for Ethnography 2017*Over a million people in the UK work in call centres, and the phrase has become synonymous with low-paid and high stress work, dictatorial supervisors and an enforced dearth of union organisation. However, rarely does the public have access to the true picture of what goes on in these institutions. For Working the Phones, Jamie Woodcock worked undercover in a call centre to gather insights into the everyday experiences of call centre workers. He shows how this work has become emblematic of the shift towards a post-industrial service economy, and all the issues that this produces, such as the destruction of a unionised work force, isolation and alienation, loss of agency and, ominously, the proliferation of surveillance and control which affects mental and physical well being of the workers.